Planʺ Amakhtonskago zaliva vʺ Tauĭskoĭ gubi︠e︡ sʺ opisi ofit︠s︡erov shkuny Vostokʺ 1875 goda / Kopirovalʺ khimicheskoi︠u︡ tushʹi︠u︡ N. Abramovʺ. Korrekt. Poupoʺl: Glotovʺ - Russia. Gidrograficheskīĭ departament; (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1876)
Relief shown by form lines. Depths shown by soundings.; Includes profile diagram of the view of Amakhtonskiy Gulf.; Profile: "Vidʺ Amakhtonskago zaliva s mi︠e︡sta i︠a︡kornoĭ stoi︠a︡nki." = View of Amakhtonskiy Gulf with anchorage places.; "No. 291" -- handwritten bottom right margin Grayscale; 1:36,000